Can perceptual differences account for enigmatic information security behaviour in an organisation?. Issue 61 (August 2016) - Kearney, W.D.; Kruger, H.A.
Highlights: Present two preceding social engineering tests and a trust survey as background and contextualisation. Present a perceptual differences study. Results offer some explanations to problems such as the privacy paradox. Propose a safe and secure information environment model. Graphical Abstract: Abstract: Information security in organisations is often threatened by risky behaviour of users. Despite information security awareness and training programmes, the human aspect of information security remains a critical and challenging component of a safe and secure information environment, and users reveal personal and confidential information regularly when asked for it. In an effort to explain and understand this so-called privacy paradox, this paper investigates aspects of trust and perceptual differences, based on empirical research. Two preceding social engineering exercises form the basis of the research project and are also presented as background information. Following the empirical work, a safe and secure information model is proposed. It is then argued that perceptual alignment of different organisational groups is a critical and prerequisite requirement to reach information security congruence between groups of people. In the context of the proposed model, the perceptual differences also offer some explanation as to why users with high levels of security awareness as well as high levels of trust in own and organisational capabilities so often fall victim to social engineering scams. The empirical work was performed at a large utility company and results are presented together with appropriate discussions.